Models for Christian Higher Education Strategies for Success in the Twenty-First Century - Hughes, Richard T; Adrian, William B. (Grand Rapids Wm. B. Eerdmans Publishing, 1997)
"This timely look at the state of Christian higher education in America contains descriptive, historical narratives that explore how fourteen Christian colleges and universities are successfully integrating faith and learning on their campuses despite t
Keywords: Christian universities and colleges -- United States -- Case studies. Church and college -- United States -- Case studies. Christian education -- United States -- Case studies